Prevention, Treatment and Eradication of NTDs by Concerted Efforts-Prognosis and Prediction: Life Sciences-Medicine - Bajaj, Mohini; Nanda, Sanju (International Journal of Life Science and Pharma Research, 2022)
Abstract: Neglected Tropical Diseases (NTDs) are diseases of poverty most prevalent in continents Africa, some parts of Asia, and the low-income regions of G20 countries. The name was given because of the neglect of the global burden of this category of diseases leading to lesser and lesser control strategies by one and all. Although medically diverse, neglected diseases share features that allow them to persist in extreme poverty. The mortality rates with these diseases are relatedly low, but morbidity rates, the main concern, are comparatively higher. This review covers the importance of the control of the NTDs at different levels of control community, national and international levels missed by many of the publications. The visual impact of most diseases is manifested in the form of disfigurement, blindness, and disabilities believed to be dreadful stigmas that people try to hide. Keeping in mind this aspect, there is an urgent need to convince most people to contribute to controlling and preventing the further spread of these diseases. Thus, motivating community-level control. The first detailed study on the global burden of these diseases and the risk factors involved was initiated by the World Bank in 1992. A follow-up study was performed in 2005. This was the basis for the start of the fight against these diseases, initially selecting the eight most affecting diseases and then gradually increasing to 13 by 2006. World Health Organization also released its first report on NTDs in 2010, compiling all the related aspects. The report was the basis for selecting diseases as targets and reached 17 diseases by 2013. Most of the reviews have not highlighted the importance of the various pharmacoeconomics and pharmacoepidemiology strategies which can be incorporated to get better results in eradicating these diseases. The main bottleneck is the inaccurate and imprecise measurement of the disease burden from the data, which does not give a clear picture of the disease. The detail of parameters selected for most of the measurement of disease burden, Disability- Adjusted Life Year (DALY), and measuring tools, which have been incorporated from time to time to meet the requirement, are also covered. The review also highlights the role played by different strata of a system for better control of these diseases.